Planning the ‘government of change’: the 2018 Italian coalition agreement in comparative perspective - Santana Pereira, J. (2019)
Coalition agreements in the Italian Second Republic have traditionally been pre-electoral, often long, compre-hensive but vague documents serving also as electoral manifestos for centre-right or centre-left coalitions. In this article, we analyse the 2018 post-electoral coalition agreement between the Movimento Cinque Stelle and Lega in comparative perspective, contrasting this agreement with former coalition programmes enforced since the mid-1990s in Italy and the pre-election manifestos published by these two political parties. The analysis reported here allow us to conclude that the first post-electoral coalition agreement in Italy is shorter than most centre-left documents, as vague as previous agreements and constitutes a compromise committing the Lega to less right-wing positions, the grillini to less progressive stances and both political forces to tone down their Eu-roscepticism. The extent by which these commitments are solid and longstanding is unknown.